Learning Biostratigraphy in University of Pembangunan Nasional “Veteran” Yogyakarta - Hari Irwanto; Satrio Esti Hapsoro (Ikatan Ahli Geologi Indonesia, 2014)
Biostratigraphy class is one of many scientific disciplines in the curriculum of Geological Engineering Department, University of Pembangunan Nasional “Veteran” Yogyakarta. The campus had been located at SWK street 104 North Ringroad, Sleman Regency, Yogyakarta Province.